Effects of Seed Priming on Growth, Chlorophyll Content, Relative Water Content and Dry Matter Distribution of Safflower (Carthamus tinctorius, cv. Gholdasht) under Salinity Stress - S. Zibai; A. Rahimi; H. Dashti (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2012)
In order to evaluate the salinity and priming effects on vegetative growth and some physiological traits of safflower, cv. Goldasht, a factorial experiment, with completely randomized blocks design and 4 replications, was conducted in Research Greenhouse of Vali-e-Asr University of Rafsanjan in 2009. Treatments included seed priming at 4 levels (no prime as control, priming with distilled water, priming with NaCl and priming with 20 Mm Ca(NO3)2 for 24 hours) and salinity at 4 levels (0, 8, 16 and 24 dS/m). Results indicated that dry weight of aerial parts, root dry weight, stem length, leaf area and head dry weight were decreased with increasing salinity. Salinity affected significantly the dry matter partitioning. As in higher salinities, more dry matter was translocated to stem and head, which was accompanied with less dry matter translocation to roots and leaves. The root/shoot ratio was significantly decreased with increasing salinity due to higher dry matter translocation to stems. Though, higher salinities decreased significantly the root dry weight. At salinity level of 24 dS/m, this safflower cultivar translocated more dry matter to shoots as compared to roots and leaves. Comparison of means showed that chlorophyll content and Spad index were decreased at higher salinity levels. Leaf area and plant height were significantly reduced only at salinities higher than 16 dS/m. The results of this experiment showed that in general, the Goldasht cultivar of safflower could tolerate salinity stress up to 16 dS/m in the vegetative stage with prominent decrease in stem and root dry weight, which could be due to some resistance mechanisms to salinity. This result must be accurately evaluated in a field experiment.